ANALISIS PENGARUH PENAMBAHAN KARBON DAN PROSES HARDENING UNTUK MENINGKATKAN NILAI EKONOMIS RODA GIGI MESIN BUBUT - Ella Sundari; Taufikurrahman Taufikurrahman (Jurnal Turbulen, 2019)
In many industrial components which made of steel such as lathe gears, most of its were usually use medium carbon steel. Because this kind of steel has high wear resistance and shock resistance, but its cost more expensive than low carbon steel. Because of this reason, the author try to use low carbon steel as a base material (raw material) for lathe gear in order to to decrease production costs. However, low carbon steel material has a carbon content of less than 0,3%, so it has poor tensile, less hardness and less friction resistance. But it strength can be increased by adding carbon, namely by means of solid carburizing and hardening process. In this study the Pack Carburizing was done at a temperature of 950oC with 1 hour holding time, and used carburizing media such as coal charcoal and Calcium Carbonat (CaCO3) as catalyst with composition of 80% + 20%. Hardening is carried out at 670oC, 760oC and 850oC. The cooling method used direct cooling method and the cooling media was used oil..And then followed by material composition test, hardness test, and micro structure test. After heat treatment, there were 0.3%, increase value in hardness. The highest harness value was at 112.66 HRB and at carburizing temperature of 850oC, Phases formed were Ferrite, Perlite and Martensite.  Keywords: Pack Carburizing, Hardening, Gear